UNJUK KERJA ROTARY DRYER PADA PROSES PENGERINGAN BIJI KOPI - Yuliati, Selastia (KINETIKA, 2018)
The dryingprocess is an important step of drying coffee. At present there are mechanical dryer for drying of coffee, oneof them is a rotary dryer for finned heater, as a heat source.Rotary system in this study was used to dry the coffee beans to a minimum water content of 12%, according to the SNI standard, calculate the thermal drying efficiency, calculate the heat transfer coefficient, and calculate the drying rate. The test parameters in this study were drying temperatures varied from 30 ËšC to 70 ËšC and a drying time of 6.5 hours. The results of this study are the value of thermal efficiency obtained ranged from 68.8 - 79%, with a decrease in water content from coffee beans ranging from 25.2 - 11.98%. The value of the heat transfer coefficient in the rotary dryer device is 390.49 - 481.63 kJ / hour. m2oC. The value of drying rate is 1.75 - 2.06 kg / hour.m2 . From the results of calculations and analysis, the optimal drying temperature to desired SNI standards is found at a drying temperature of 70ËšC with a drying time of 390 minutes. The performance of the rotary dryer is very good with thermal efficiency values above 60%